Active Learning: 101 Strategies To Teach Any Subject - Silberman, Mel (Prentice-Hall, 1996)
This book contains specific, practical strategies that can be used for almost any subject matters to promote active learning. It brings together in one source a comprehensive collection of instructional strategies, with ways to get students to be active from the beginning through activities that build teamwork and get students thinking about the subject matter. There are techniques for full-class and small-group instruction, and methods for reviewing and assessing what students have learned. Although most of the strategies will apply to any age level, the book is directed at those who teach older children and adults, especially teachers in middle school, high school, college, and adult education centers. The 101 strategies are grouped into the following areas: (1) "Introducing Active Learning"; (2) "How To Get Students Active from the Start"; (3) "How To Help Students Acquire Knowledge, Skills, and Attitudes...Actively"; and (4) "How To Make Learning Unforgettable." (SLD)